The Effect of Mind Map Integration in the Problem Based Learning Model on Creative Thinking of VIII Class Students - Utharia Darmayanti; Sri Wulandari; Fitra Suzanti (Universitas Riau, 2021)
The 2013 curriculum requires teachers to integrate higher-order thinking skills. One of them is creative thinking. Mind map integration in Problem Based Learning (PBL) is thought to be able to assist students in improving creative thinking. This study aims to determine the effect of increasing creative thinking through the integration of mind maps in PBL on eighth grade students of SMPN 25 Pekanbaru. This type of research is quasi-experimental. The research population was class VIII SMPN 25 Pekanbaru. The research sample consisted of class VIII.1 as the experimental class and class VIII.2 as the control class. Data in the form of pretest and posttest. N-gain analysis was conducted to see the increase in student scores and MANOVA was used to examine the effect of mind maps in PBL on students creative thinking abilities. The average value of creative thinking is better in the experimental class which is 78.08 in the digestive system material with N-gain relatively close to high, namely 0.68 while in the control class only 54.88 is sufficient category. The MANOVA test also shows that there is an effect of mind maps in PBL on the creative thinking ability of class VIII SMPN 25 Pekanbaru with a significance value of 0.000 <0.05. This shows that the application of mind map integration to PBL is able to improve the creative thinking skills of SMP Negeri 25 Pekanbaru students.